2021
DOI: 10.3390/biom11020165
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Protects Neurons in the Cerebellum of Rats through Mitigating Oxidative Stress and Inflammation Following High-Fat Diet Supplementation

Abstract: High-fat diet (HFD) is a major problem causing neuronal damage. Thymoquinone (TQ) could regulate oxidative stress and the inflammatory process. Hence, the present study elucidated the significant role of TQ on oxidative stress, inflammation, as well as morphological changes in the cerebellum of rats with HFD. Rats were divided into three groups as (1) control, (2) saturated HFD for eight weeks and (3) HFD supplementation (four weeks) followed by TQ 300 mg/kg/day treated (four weeks). After treatment, blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Interestingly, fisetin, as well as chelerythrine are also reported to be important supplements for poultry to avoid heat stress-associated morbidities and spotty liver disease, respectively [ 90 , 91 ]. Lastly, animal studies on Lycium barbarum polysaccharides, osthole and thymoquinone have also shown satisfactory tolerability in vivo and those products hold promise to the manufacture of relevant supplements [ 92 , 93 , 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, fisetin, as well as chelerythrine are also reported to be important supplements for poultry to avoid heat stress-associated morbidities and spotty liver disease, respectively [ 90 , 91 ]. Lastly, animal studies on Lycium barbarum polysaccharides, osthole and thymoquinone have also shown satisfactory tolerability in vivo and those products hold promise to the manufacture of relevant supplements [ 92 , 93 , 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of this study, TQ has a neuroprotective effect on the apoptosis of cerebellar granule neurons (CGNs) due to β-amyloid peptide 1-40 (13). In another recent study, the antioxidant effect of TQ was investigated in the cerebellum of rats who had consumed a high-fat diet (HFD) (1). Since HFD is accepted as a major problem for neuronal damage, oxidative stress markers were measured in the serum of those rats to investigate the meliorative effect of TQ after 4 weeks of HFD supplementation.…”
Section: Introductionmentioning
confidence: 93%
“…Since HFD is accepted as a major problem for neuronal damage, oxidative stress markers were measured in the serum of those rats to investigate the meliorative effect of TQ after 4 weeks of HFD supplementation. Alrafiah reported that the treatment with TQ reduced the inflammation and ameliorated the antioxidant enzymes implying an improvement in the HFD-induced neuronal damage in cerebellum tissues (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations